The Significance of Self-Confidence in the Success of Referees During Football Match Officiating - Permadi, Asep Angga; Frahmawati, Ima; Pramdhan, Kartono; ishak, M; Fernando, Ricky; Shahril, Mohd Izwan (Musamus Journal of Physical Education and Sport (MJPES), 2024)
Self-confidence is a facet of personality encompassing an individual's qualities, skills, and abilities. Objective. The objective of this study is to ascertain the correlation between a referee's self-confidence and the efficacy in officiating a football match. Material and Methods. This study employs a descriptive methodology. The author employs a random selection technique for the sample of male referees possessing a Football referee license status at PSSI Garut. The research design employs a one-shot approach. The test employed is a questionnaire assessing self-confidence and the capacity to effectively conduct a football match. Data analysis employs validity tests, reliability tests, normalcy tests, percentage tests, t-tests, and correlation tests. Results. The research data processing revealed that the self-confidence level of PSSI Garut referees is categorized as sufficient, while their success in officiating PSSI Garut matches is classified as good. Furthermore, there exists a moderate correlation coefficient between self-confidence and success in leading PSSI Garut matches. It is advised that football referees possess strong self-confidence in their ability to successfully officiate PSSI Garut matches. The study's merits include a lucid methodology and thorough outcomes. Nevertheless, Conclusions. The results of this study may lack generalizability to other situations, as they are limited to a sample of reviewers at PSSI Garut. Subsequent research should encompass an expanded sample from other regions and investigate supplementary factors that contribute to referee success, such as experience, training, and psychological conditions.